Digital Repositories as Knowledge Infrastructure: Institutional Management Strategies in the Open Access Era - Primus Sanbein (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2026)
Digital repositories have increasingly been recognized as integral elements of the knowledge infrastructure in higher education and research environments. Their role extends beyond mere storage of scholarly works to include preservation, dissemination, and equitable access to academic knowledge in accordance with open-access principles. However, many institutional repositories continue to face persistent challenges, including fragmented governance structures, limited system interoperability, suboptimal metadata practices, and low user engagement. To address these issues, this study adopts a Conceptual Literature Review (CLR) approach to synthesize interdisciplinary insights on repository management in the context of open access. The findings reveal four interconnected strategic dimensions that influence repository sustainability: governance and policy, technological infrastructure, institutional capacity and human resources, and user-oriented services. These dimensions are subsequently integrated into a conceptual model that emphasizes their systemic interrelationships within institutional knowledge management. This study reframes digital repositories not simply as technical storage platforms, but as governance-driven knowledge infrastructures that facilitate the circulation and strategic utilization of scholarly outputs. The proposed framework provides analytical direction for enhancing institutional preparedness and ensuring the long-term sustainability of repositories within the broader open science landscape.